PERTUMBUHAN DAN HASIL EMPAT VARIETAS KACANG HIJAU (Vigna radiata L.) PADA SISTEM TUMPANGSARI DENGAN BERBAGAI JARAK TANAM JAGUNG - Edhi Turmudi; Nurga Henni Safitri; Widodo Widodo (BPFP Universitas Bengkulu, 2020)
[GROWTH AND YIELD OF FOUR VARIETIES OF MUNG BEAN (Vigna radiata L.) IN INTERCROPPING SYSTEM WITH VARIOUS CORN PLANT SPACING]. Efforts to increase the productivity of mung beans (Vigna radiata L.) can be done by implementing an intercropping system and using superior varieties. Corn plants need high nitrogen and mung bean plants can fix nitrogen from the free air so that corn plants can take advantage of the excess nitrogen from mung beans. The purpose of this study was to determine the best mung bean varieties in the intercropping system with a various spacing of maize. The research was conducted in October-December 2018, in Pematang Gubernur village, Muara Bangkahulu, Bengkulu. The experiment in this study used a split-plot design with the main plot spacing of maize that was 60 cm x 30 cm, 90 cm x 30 cm, 120 cm x 30 cm, subplots were mung bean varieties (Vima-1, Vima- 2, Vima-3, and Kutilang) with 3 repetitions. Repeated 3 times, then 36 experimental units were obtained. The results showed that the four varieties of mung beans planted intercropping with a various spacing of maize showed different yield responses. Varieties of Vima-1 and Vima-3 gave the highest seed yields at a maize spacing of 60 cm x 30 cm. The Vima-2 variety was at a spacing of 90 cm x 30 cm, while the Kutilang variety was at 120 cm x 30 cm spacing. The four mung bean varieties were suitable for intercropping with maize with a yield/plot (NYi)> 0.5.